Cardiac Response to Exercise in Normal Ageing: What Can We Learn from Masters Athletes? - Beaumont, A. (Curr Cardiol Rev, 2018)
BACKGROUND: Ageing is associated with an inexorable decline in cardiac and vascular func-tion, resulting in an increased risk of Cardiovascular Disease (CVD). Lifestyle factors such as exer-cise have emerged as a primary therapeutic target in the prevention of CVD, yet older individuals are frequently reported as being the least active, with few meeting the recommended physical activity guidelines. In contrast, well trained older individuals (Masters athletes) have superior functional ca-pacity than their sedentary peers and are often comparable with young non-athletes. Therefore, the 'masters' athlete may be viewed as a unique non-pharmacological model which may allow researchers to disentangle the inexorable from the preventable and the magnitude of the unavoidable 'true' reduc-tion in cardiac function due to ageing. CONCLUSION: This review examines evidence from studies which have compared cardiac structure and function in well trained older athletes, with age-matched controls but otherwise healthy